TNF alpha blockade in rheumatoid arthritis: rationale, clinical outcomes and mechanisms of action. - Elliott, M; Feldmann, M; Maini, R (1995)
Tumor necrosis factor alpha (TNF alpha) is a cytokine with many biological functions of relevance to inflammatory disease. Although only one of several inflammatory mediators produced in abundance in rheumatoid arthritis (RA), experimental data suggest that it is in a dominant position within a cytokine hierarchy and is therefore a prime target for directed immunotherapy in this disease. We have targeted TNF alpha in vivo using a chimerised monoclonal anti-TNF alpha antibody and have now demonstrated beneficial responses to treatment in three different clinical trials. The results confirm that TNF alpha is of central importance in the inflammatory process in RA and define a new treatment strategy in this disease.